2016
DOI: 10.7818/ecos.2016.25-2.08
|View full text |Cite
|
Sign up to set email alerts
|

Dendrochronology in Neotropical dry forests: methods, advances and applications

Abstract: Artículo publicado en Open Access bajo los términos de Creative Commons attribution Non Comercial License 3.0. MONOGRÁFICO: El bosque seco neotropical de la provincia Ecuatoriana: un pequeño gran desconocido ecosistemas REVISTA CIENTÍFICA DE ECOLOGÍA Y MEDIO AMBIENTE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
4
0
4
Order By: Relevance
“…La no diferenciación puede deberse a que los árboles provienen de una zona en la que están en continuo crecimiento durante todo el año y no desarrollan un periodo de dormancia debido a la ausencia de una marcada estacionalidad (Zumaeta et al, 2008;Rosero, 2012;Mendivelso et al, 2016) Los valores cuantitativos obtenidos para las traqueidas axiales (longitud, ancho, diámetro de lumen y espesor de pared) en ambas especies fueron similares a los obtenidos por Vásquez (2010) y García et al, (2017, pero se determinó que el diámetro de lumen fue estadísticamente superior en P. harmsiana.…”
Section: Discussionunclassified
“…La no diferenciación puede deberse a que los árboles provienen de una zona en la que están en continuo crecimiento durante todo el año y no desarrollan un periodo de dormancia debido a la ausencia de una marcada estacionalidad (Zumaeta et al, 2008;Rosero, 2012;Mendivelso et al, 2016) Los valores cuantitativos obtenidos para las traqueidas axiales (longitud, ancho, diámetro de lumen y espesor de pared) en ambas especies fueron similares a los obtenidos por Vásquez (2010) y García et al, (2017, pero se determinó que el diámetro de lumen fue estadísticamente superior en P. harmsiana.…”
Section: Discussionunclassified
“…These studies focused on the northern and central mountainous areas of the country, mostly in the Sierra Madre Occidental complex, which contains many temperate forests. A few studies in tropical ecosystems were found, whose research can be considered incipient in relation to other Latin-American countries [16,21,30,31]. [28].…”
Section: Resultsmentioning
confidence: 99%
“…In general, we expected to find more conifers and deciduous broadleaf tree species from seasonal climate zones in these studies. This is due to their growth rings being better defined, which facilitates their synchronization or cross-dating and subsequent measurement, compared with tropical forests in which tree-ring delimitation and cross-dating are not so simple [1,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…La xilogénesis incluye el estudio de los componentes estructurales de la madera y su fenología (Mendivelso et al, 2016). La formación de la madera refleja las ganancias de carbono en el ecosistema.…”
Section: Xilogénesisunclassified